Implementation of Special Autonomy Policies in Improving Community Welfare in Jayawijaya Regency, Papua Highlands Province - Rumere, Immanuel Yunias A. R.; Suradinata, Ermaya; Rowa, Hyronimus; Lambelanova, Rossy (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The phenomenon that is the object of research is the implementation of special autonomy policies in improving people's welfare in Jayawijaya Regency, Papua Mountains Province. This study aims to discuss the implementation of special autonomy policies in improving people's welfare in Jayawijaya Regency, Papua Mountains Province and to obtain a model from the analysis of the implementation of special autonomy policies in improving welfare in Jayawijaya Regency, Papua Mountains Province. This research method uses a qualitative descriptive method. The selection of informants was carried out using a purposive sampling technique consisting of elements of government leaders, traditional/community leaders, academics and stakeholders totaling 7 informants. By using Grindle's policy implementation theory. The results of the study indicate that the implementation of the policy to improve the welfare of the people of Jayawijaya Regency can be done through the provision of educational, health, economic and other social assistance to the people of Jayawijaya Regency and the Asymmetric Diversion Policy Implementation Model for Improving Community Welfare through the Provision of Educational, Health, Economic and Other Social Assistance to the People of Jayawijaya Regency which synergizes the implementation of asymmetric regional policies on the amount of social assistance budget allocation from the APBD for each budget year and asymmetric regional head policies on the provision of social assistance with the implementation of regulations and laws in regulating the provisions, procedures and methods for providing social assistance according to objective conditions of geographical remoteness, sociological backwardness and limitations of community human resources.